Fresno County Bar Association's 110th Annual Bar Banquet Held At Elks Lodge - Watkins, Howard::::::::: (1982)
David St. Louis and Doug MacArthur doing Star Wars skit; Doug Jensen in background 5080 E. Kings Canyon Road, Fresno